Quality and Accreditation Requirements for the Curriculum Development of Special Education Departments as Perceived by Faculty Members - Omer A. Agail (University of Science and Technology, Yemen, 2017)
The current study aimed to determine the quality and accreditation requirements, according to the NCAAA, for the curriculum development of the departments of Special Education as perceived by faculty members. Moreover, the study aimed to determine the relationship between the faculty awareness and other factors such as, gender, academic rank, teaching experience, participation in curriculum development, attendance of workshop, and participation in program development committees. The researcher created a survey to answer the research questions. A sample of (45) faculty members was chosen randomly from three main universities: King Khalid university, Jazan University, and Najran University.  Statistical methods were used, including mean, frequencies, one sample t-test, one way ANOVA. The results indicated that the participants' awareness toward curriculum development requirements was generally very low, because of the limited number of faculty members and the newly established departments. It was recommended that quality culture should be disseminated, and moral and material support should be provided to the programs in these departments.  Keywords: Study programs, Quality, Accreditation, Special education.